Carbon fiber damage evolution under flame attack and the role of impurities. (29th June 2022) - Chávez‐Gómez, Pablo; Pelzmann, Tanja; Hall, Darren R.; Chilian, Cornelia; Laberge Lebel, Louis; Robert, Étienne
Abstract: Carbon fibers (CFs) are prone to extensive oxidation under fire attack, for instance, in an aircraft fire scenario. This work addresses the damage mechanisms observed on polyacrylonitrile (PAN)‐based CFs with different microstructure exposed to open flames. A fixed‐point technique was developed to follow‐up individual CFs by means of time‐controlled insertion into premixed methane/air flames, followed by scanning electron microscopy (SEM) and energy‐dispersive X‐ray spectroscopy (EDS) analyses. Besides diameter reduction, three localized damage mechanisms were discerned in the presence of impurities, which were quantified by neutron activation analysis (NAA). Severe pitting was ascribed to catalytic oxidation mainly caused by alkali and alkaline earth metals. After an initial period where catalytic reactions between impurities and the carbon surface dominate, the flame stoichiometry governed the CF gasification process, with lean flames being much more aggressive than rich ones. A second mechanism, channeling, was caused by mobile metallic impurities. Some impurities showed an opposite effect, lowering reactivity and thus preventing further catalysis. Amorphous damage with a skin‐peeling effect is believed to be the result of localized impurities at high concentrations and microstructural variations. Hindrance or synergistic effects between impurities are discussed. Finally, apparent axial pit growth rates were determined and compared with other carbonaceous materials, revealing a strong influence of impurities and the flame reactive atmosphere on CF oxidation.